The Transformation of Inorganic and Methylmercury in the Presence of l-Cysteine Capped CdSe Nanoparticles - Shi, Xiangming; Zhao, Jing; Wang, Yongchen; Mason, Robert P. (Frontiers in Environmental Chemistry, 2021)
Transformations of mercury (Hg) forms in the aquatic environment is a crucial aspect of Hg fate, transport and the bioaccumulation of methylmercury (CH3Hg; MeHg), which is the form that drives most human health concerns. Transformations between Hg forms on surfaces have been inadequately studied andbut here we report on the interaction of inorganic Hg (HgII) and MeHg with chalcogenide nanoparticles (NPs); specifically L-cysteine capped CdSe nanocrystals. The study sheds light on the transformation of the Hg species and the interaction mechanisms, by examining the product composition, reaction mass balance and the distribution between the liquid and solid phase. The results showed that the quenching of the photoluminescence (PL) of CdSe NPs was greater for HgII than MeHg, and that HgII caused significant PL quenching even when its concentration was in the nM range. Over 90% of HgII was found associated with the solid phase while most MeHg existed in the liquid phase in the experimental solutions. No dimethylmercury ((CH3)2Hg; DMeHg) was produced from the interaction of MeHg and the NPs, in contrast to findings with microparticles. However, a fast and complete MeHg transformation into HgII occurred when the MeHg + NPs mixture was exposed to light. A scheme for the MeHg degradation was derived and is presented, and it was concluded that the precipitation of HgSe accelerated the MeHg degradation. These results provide insight into the abiotic pathways for MeHg degradation in environmental waters in the presence of NPs.